ZNO-Ag/PS and ZnO/PS Films for Photocatalytic Degradation of Methylene Blue - Hassan Khuder Naji; Amjed Mirza Oda; Wesam Abdulaljeleel; Hussein Abdilkadhim; Rawaa Hefdhi (Indonesian Journal of Chemistry, 2020)
Two films of ZnO-Ag/polystyrene (ZnO-Ag/PS) and ZnO/polystyrene (ZnO/PS) have been prepared to evaluate the photodegradation ability of stabilized catalysts. The efficiency of ZnO improved against recombination of electron-hole pair by modification of catalyst surface with Ag photodeposition to be more resistant towards photocorrosion. ZnO-Ag catalyst was characterized by SEM and EDS analysis to show high roughness of this catalyst and Ag deposited on the surface was 2% (molar ratio). ZnO-Ag/PS and ZnO/PS composites were made as films and were then analyzed by FTIR spectra that showed the interaction of ZnO and ZnO-Ag with polystyrene appeared in the range of 400–620 cm–1, XRD pattern indicated the presence of Ag nanoparticles on the surface of ZnO and ZnO/PS film has maximum absorbance at 376 nm in UV-VIS spectra. This value shifted to 380 nm because of the photodeposition. The photocatalytic reaction was depicted using methylene blue (MB) in the UV-irradiation action of stacked films in MB solution. The result showed that both ZnO-Ag/PS and ZnO/PS films gave efficiency to remove MB by 97% and 70%, respectively. The reusability test of the films showed that ZnO-Ag/PS was more resistant than ZnO/PS. The presence of Ag also increased the efficiency in photodegradation and resistance against photocorrosion.